2018
DOI: 10.3390/jmmp2030050
|View full text |Cite
|
Sign up to set email alerts
|

Towards Sustainable Machining of Inconel 718 Using Nano-Fluid Minimum Quantity Lubrication

Abstract: Difficult-to-cut materials have been widely employed in many engineering applications, including automotive and aeronautical designs because of their effective properties. However, other characteristics; for example, high hardness and low thermal conductivity has negatively affected the induced surface quality and tool life, and consequently the overall machinability of such materials. Inconel 718, is widely used in many industries including aerospace; however, the high temperature generated during machining i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(28 citation statements)
references
References 32 publications
2
25
0
1
Order By: Relevance
“…The authors concluded that the cutting performance and surface quality improved due to the interface bonding between the tool and workpiece surface. They also extended the study to investigate the tool performance and chip morphology during machining Inconel 718 by using MWCNTs and Al 2 O 3 nanofluid [23,24]. The results indicated the enhancement of MQL cooling and lubricating capabilities, which contribute to improve the machining performance compared to the case with no nano-additives.…”
Section: Introductionmentioning
confidence: 93%
“…The authors concluded that the cutting performance and surface quality improved due to the interface bonding between the tool and workpiece surface. They also extended the study to investigate the tool performance and chip morphology during machining Inconel 718 by using MWCNTs and Al 2 O 3 nanofluid [23,24]. The results indicated the enhancement of MQL cooling and lubricating capabilities, which contribute to improve the machining performance compared to the case with no nano-additives.…”
Section: Introductionmentioning
confidence: 93%
“…However, this can generate a higher thrust force due to a very high local temperature at the tool interface [26]. Different studies [27,28,29,30] proved that using MQL-nanofluid was effective in improving overall machinability, as it supports the tribology and heat transfer of the cutting operations.…”
Section: Introductionmentioning
confidence: 99%
“…The applied nano-mist with compressed air shows capabilities in penetrating into the tool–workpiece interface area, and reduces the severity of the induced heat during machining operation. In addition, the employed nano-mist acts like rollers and causes a noticeable effect in the frictional behavior of the cutting operation, as has been discussed in the literature [29,30,31].…”
Section: Resultsmentioning
confidence: 99%